Примусові заходи виховного характеру як інститут кримінального права України - Кузьменко, Олександр Васильович (НТУ "ХПІ", 2018)
У цій статті аналізується сучасний стан вивчення проблеми пошуку оптимальних, науково обґрунтованих шляхів вдосконалення вітчизняної системи примусових заходів виховного характеру. Здійснюється огляд теоретичних і експериментальних досліджень українських та зарубіжних науковців, що працюють у сферах правознавства, психології, педагогіки й соціології. Використовуються матеріали судової практики, дані правової статистики й відповідний міжнародний досвід. Аналізується правова природа примусових заходів виховного характеру за Кримінальним кодексом України, здійснюється спроба визначення перспектив розвитку вітчизняної системи цих заходів. Наводяться доводи на користь доцільності оновлення зазначеної системи. Підтримується ідея створення якісно нової системи примусових заходів виховного характеру, що будуть застосовуватися до неповнолітніх, звільнених від кримінальної відповідальності. Наводяться аргументи на підтримку думки про необхідність доповнення чинної системи кримінальних покарань для неповнолітніх новими їх видами, окремі з яких будуть створені на основі певних примусових заходів виховного характеру.

The author examines the current state of studying the problem of finding optimal, scientifically grounded ways to improve the domestic system of compulsory measures for the re-education of juvenile offenders. The author reviews theoretical and experimental studies of Ukrainian and foreign scholars working in the fields of law, psychology, pedagogy and sociology. Researcher use case law, legal statistics and data relevant international experience. The author analyzes the legal nature of compulsory educational measures under the Criminal Code of Ukraine, attem pts to determine the prospects for the development of the domestic system of these measures. The researcher formulates the arguments in favor of the expediency of updating the specified system. The author supports the idea of creating a qualitatively new system of compulsory measures of educational nature that will be applied to minors exempted from criminal liability. The researcher formulates arguments in support of the idea of the need to supplement the existing system of criminal penalties for minors by their new types, some of which will be based on certain coercive measures of educational nature. The researcher expresses and justifies the proposal on the need to improve the domestic system of compulsory educational measures applicable to minors exempted from punishment. The author evaluates the effectiveness of certain coercive measures of educational nature, provided by the current legislation of Ukraine on criminal liability.
Compulsory measures of upbringing as an institution of criminal law of Ukraine
Keywords: кримінальне покарання; кримінальна відповідальність; злочин; суспільно небезпечне діяння; Кримінальний кодекс України; система покарань; minor child; criminal punishment; criminal liability; socially dangerous act